Pengembangan Instrumen Penilaian Autentik pada Pembelajaran - Boini Boini; Asnawi Asnawi; Muhamad Tisna Nugraha; Moh.Ainin Moh.Ainin (At Turots: Jurnal Pendidikan Islam, 2023)
This Research and Development aims to develop assessment instruments that are based on the realm of knowledge and attitudes to assess student performance and measure student abilities in the process of learning activities. This Research and Development also aims to develop authentic assessment learning tools with a scientific approach to learning. The problem formulation presented in this research is to describe (1) How can an authentic and appropriate scientific approach be applied in teaching using authentic and appropriate assessment? (2) What are the results of developing authentic and relevant scientific inquiry learning instruments? As for the research objectives which can be summarized from the introductory presentation, discussion and problem formulation, the common thread can be drawn from the objectives of this research: To find out how an authentic and appropriate scientific approach can be applied in teaching by using authentic and appropriate assessments? To find out what the results of developing authentic and relevant scientific inquiry learning instruments are? Authentic assessment learning tools developed with a scientific approach have been validated by experts and practitioners and tested to obtain results that are suitable for use as intended. The research results show that authentic assessment learning tools with a scientific approach are rational and empirical, valid and reliable, including attitude assessment instruments: spiritual attitude observation sheets, rubrics and social attitude observation sheets. Cognitive assessment instruments include: test outline, competency test, rubric and competency test assessment sheet. The skills assessment instruments used are: performance tests, and rubrics and performance test assessment sheets.